Eco-friendly larvicide source from Acacia auriculiformis and its antimicrobial activity against clinical pathogens - Subbaraj Dinesh Kumar; Ponnuraj Srinivasan; Manickam Rajalakshmi; Rajendran Gowtham Raj; Karuppannan Sathiyamurthy (International Journal of Phytomedicine, 2017)
Mosquito remains as a global threat for millions of lives since they serve as vector for most of the deadly pathogens and parasites. Several methods such as indoor spraying, insecticidal usage, and nets are employed to evade mosquito threat. However, the chemicals present in such compositions not only have negative impact on the human health and environment but also paves the way for the development of resistance in the insect vectors. Under such circumstances, novel and safer alternative tools have been recently researched to improve mosquito control. Medicinal plants species have been screened as a potential source for secondary metabolites with larvicidal and antimicrobial properties. In view of such fact, the present study investigated the solvent extracts of A. auriculiformis for its antimicrobial, antioxidant and larvicidal properties against the malarial and Japanese encephalitis vector Aedes albopictus and Culex quinquefasciatus respectively. Results evidently showed that the ethanol, ethyl acetate, and water extracts inhibited the test pathogens significantly as compared to the other extracts at sub-MIC levels. DPPH and FRAP antioxidant studies elucidate, strong antioxidant potential of the ethanol and chloroform extracts of A. auriculiformis. TLC profile of the ethanol extract showed six prominent bands with respectively coloured band patterns in the UV spectrum which corroborated with the presence of more than one active principles in the extract. The larvicidal activity assay revealed that the ethanol extract significantly inhibited the mosquito vectors with an LC50 of 6.1 and 4.2 µg/ml respectively. Notably, the toxicity assay on the non target organism G. affinis showed low mortality at the tested concentrations (LC50 = 1670 µg/ml) which is ten times greater than the lethal concentration to the mosquito species. Overall, this study highlights the preliminary results which substantiates that A. auriculiformis is an important source of eco-friendly and biodegradable larvicides against two important mosquito vectors with low toxicity against non-target organism.